2020
DOI: 10.1111/ibi.12846
|View full text |Cite
|
Sign up to set email alerts
|

Increasing temperatures increase the risk of reproductive failure in a near threatened alpine ground‐nesting bird, the Cape Rockjumper Chaetops frenatus

Abstract: A major cause of reproductive failure in birds is nest predation. Predation risk depends on predator type, as predators vary in their ecology and sensory modalities (e.g. visual vs. olfactory). Snakes (generally olfactory predators) are a major nest predator for small birds, with predation strongly associated with higher temperatures. We investigated nest survival in a ground‐nesting alpine species, the Cape Rockjumper Chaetops frenatus, endemic to alpine fynbos in southwestern South Africa. We collected 3 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 50 publications
2
10
0
Order By: Relevance
“…This finding is consistent with negative effects of high temperatures on reproduction found in other arid-region vertebrates (e.g. common fiscals Lanius collaris [Cunningham et al 2013] predator-prey interactions as found here requires further scrutiny in other species (Oswald et al 2020).…”
Section: The Effects Of Temperaturesupporting
confidence: 91%
“…This finding is consistent with negative effects of high temperatures on reproduction found in other arid-region vertebrates (e.g. common fiscals Lanius collaris [Cunningham et al 2013] predator-prey interactions as found here requires further scrutiny in other species (Oswald et al 2020).…”
Section: The Effects Of Temperaturesupporting
confidence: 91%
“…Therefore, the combination of the heart rate monitoring and continued presence of adults in many nests gives us confidence that the mortality of embryos was a direct effect of the heat, rather than an indirect effect caused first by parental desertion. An alternative reason for greater mortality with increasing temperature is higher levels of predation, as suggested by a recent study of a ground-nesting species in Africa, which found that reproductive failure was greater at higher ambient temperatures due to predation by snakes (Oswald et al 2020). We found little evidence of predation of the nests in our study.…”
Section: Discussionsupporting
confidence: 54%
“…We present and compare the results of both phylogenetically controlled and conventional analyses in line with recommendations from the literature (Oswald et al, 2020;Schluter, 2000;Swanson & Bozinovic, 2011). We first used conventional analysis, fitting general linear models to response variables (e.g., clutch size, incubation period, nestling period, and nest success) as predicted by nest concealment, with body mass as a potential confounding effect.…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 99%
“…often have no relation between nest concealment and nest success when their nests are accessible (Conover et al, 2010;Oswald et al, 2020).…”
mentioning
confidence: 99%